1983
DOI: 10.1002/ar.1092070410
|View full text |Cite
|
Sign up to set email alerts
|

The sensory innervation of the ovary: A horseradish peroxidase study in the rat

Abstract: Injections of horseradish peroxidase (HRP) into the right or left ovary of the rat produced labeling of perikarya in both nodose ganglia and ipsilateral dorsal root ganglia (DRGs) from T10 to L2. The greatest concentration of labeled cells was in T13 and L1, DRGs. It is suggested that visceral afferent fibers from the ovary may mediate visceral reflexes that modulate ovarian function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 27 publications
3
50
1
Order By: Relevance
“…These results are in line with previous animal studies demonstrating that the vagus nerve can indeed project below the transverse colon (splenic flexure), providing sensory innervation to the kidney (Gattone et al, 1986), ovary (Burden et al, 1983) and even portions of the female reproductive tract (uterus, cervix) (Ortega-Villalobos et al, 1990, Hubscher and Berkley, 1995, Collins et al, 1999.…”
Section: Nodose Ganglion Labelingsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in line with previous animal studies demonstrating that the vagus nerve can indeed project below the transverse colon (splenic flexure), providing sensory innervation to the kidney (Gattone et al, 1986), ovary (Burden et al, 1983) and even portions of the female reproductive tract (uterus, cervix) (Ortega-Villalobos et al, 1990, Hubscher and Berkley, 1995, Collins et al, 1999.…”
Section: Nodose Ganglion Labelingsupporting
confidence: 92%
“…Despite the view that the vagus nerve does not innervate viscera caudal to the transverse colon, numerous experimental studies have demonstrated that it also provides sensory innervation to the majority of the pelvic viscera (Burden et al, 1983, Gattone et al, 1986, Jancso and Maggi, 1987, Ortega-Villalobos et al, 1990, Altschuler et al, 1993, Hubscher and Berkley, 1995, Collins et al, 1999, Vizzard et al, 2000. Even though the vagus nerve has such widespread projections, SCI does not disconnect the anatomical relationship the nerve has with the tissue it innervates.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…However, although several histological studies have described the innervation of vagal parasympathetic and sympathetic nerves including both afferents and efferents to the ovary, the roles of these autonomic nerves in ovarian function have not been sufficiently clarified [1][2][3][4][5][6]. Histological studies by Burden et al [1,7] demonstrated that autonomic nerves enter the ovary via hilar perivascular plexuses, and tiny branches from these plexuses extend into the contiguous steroidogenic interstitial gland cells. Autonomic nerves to the rat ovary reach the organ by two routes: the ovarian plexus nerve (OPN) along the ovarian artery and the superior ovarian nerve (SON) in the suspensory ligament [8,9].…”
mentioning
confidence: 99%
“…The effects are related to functional changes in the adrenal medulla and do not depend on the sensitive of the afferent fibers (Ulrich-Lai et al, 2006). The ovaries receive motor innervations from the sympathetic and the parasympathetic system via the vagus nerve, and possess afferent fibers travelling sympathetic and vagal routes (Burden et al 1983;Klein and Burden, 1988, Gerendai et al, 2000. The vagus nerve connects the ovaries with the area postrema, the nucleus of the solitary tract, the dorsal vagal complex, the parapyramidal nucleus, A1, A5, and A7 -cell groups, the caudal raphe nuclei, the hypothalamic paraventricular nucleus, the lateral hypothalamus, the Barrington's nucleus, the locus coeruleus, the periaqueductal gray, and the dorsal hypothalamus.…”
Section: Ovarian and Adrenal Innervationsmentioning
confidence: 99%